An operational assessment of housekeeping services in fulfilling guest requests: A case study of Rby Bali - Ni Made Kami Elisa Putri; I Komang Mahayana Putra; Majid Wajdi; Muhammad Ahmad Mazher (Yayasan Mitra Persada Nusantara, 2025)
This study aims to evaluate the handling of guest requests in the housekeeping department of RbyA Bali, a five-star resort in South Kuta, Bali. The primary objectives are to analyse how guest requests are managed operationally and to identify the challenges faced by the housekeeping staff in adhering to the Standard Operating Procedures (SOPs). A qualitative descriptive method was employed in this research, using observation, interviews with housekeeping coordinators and staff, and documentation review as data collection techniques. The analysis followed a thematic approach to identify patterns and categories in request handling processes and challenges. The results reveal that while the hotel has a structured SOP in place, there are recurring issues in communication flow, time efficiency, and coordination between departments that affect service consistency. Some guest requests—such as extra amenities, turndown services, or special room arrangements—are not always fulfilled promptly, often due to a mismatch in workforce allocation or lack of digital coordination tools. Despite these challenges, the staff demonstrates a high commitment to guest satisfaction. The study concludes that effective handling of guest requests is crucial to enhancing service quality and maintaining a luxury brand image. Improvements are needed in administrative systems, training, and inter-departmental communication. The findings are expected to support operational refinement and serve as a reference for hospitality students and professionals seeking to improve guest service experiences.